(untitled) (Revista científica Olimpia, 2020)
Inside the set of diseases that they are attended by means of the utilization of physical exercise, we have the orthopedic deformities with a height percent of incidence, find in the cuban school people. An insufficient progress in the treatment of the orthopedic foot deformities in school patients of the therapeutic area Mártires de Minas was registered. The objective of investigation is: Elaborating adapted exercises using therapeutic slippers for the treatment of the supine foot and deep deformity of the therapeutic area Mártires de Minas. The investigation is taking place at the therapeutic area Mártires de Minas. The solution to everything presented was the confection to a set of adapted exercises with the utilization of some therapeutic slippers, that the patient may accomplish the treatment of the orthopedic foot deformities in the class section that were corresponding. As one has principal results that the supination that was existing in the patient’s feet disappeared almost completely, and the foot deep classification was improved a small percent.